Cálculo de blindajes - Placer, Alejandro E.; Biaggio, Alfredo Lucio; Arbor, Agustín; Mudano, Enrique; Bianchi, Ángel J. (Comisión Nacional de Energía Atómica; Argentina, 1975)
Fil: Placer, Alejandro E. Comisión Nacional de Energía Atómica; Argentina